2013
DOI: 10.5961/jhes.2013.071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anxiety levels of nursing students while preparing their thesis

Abstract: Araştırma Ege Üniversitesi Hemşirelik Yüksekokulu tez hazırlayan 3. ve 4. sınıf öğrencilerinin kaygı düzeylerini ve etkileyen faktörleri incelemek amacıyla tanımlayıcı bir çalışma olarak yapılmıştır. Araştırma Ege Üniversitesi Hemşirelik Yüksekokulu 3. sınıf ve 4. sınıfta okuyan 142 öğrenci ile yürütülmüştür. Araştırma verileri araştırmacılar tarafından oluşturulan soru formu ve Durumluluk-Sürekli Kaygı Ölçeği ile toplanmıştır. Araştırmaya katılan öğrencilerin %52,1'i 23 yaş üzerinde, %53,5'i 4. sınıfta okumak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…In studies conducted with nursing students, it was found that students' anxiety toward conducting research was moderate (Kes & Şahin, 2019) or high (Gerçek et al, 2016;Güleç & Saruhan, 2013). In most of these studies, more than half of the participants affirmed that conducting research made them nervous, anxious and scared (Amoo & Gbadamosi, 2021;Muzzmal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted with nursing students, it was found that students' anxiety toward conducting research was moderate (Kes & Şahin, 2019) or high (Gerçek et al, 2016;Güleç & Saruhan, 2013). In most of these studies, more than half of the participants affirmed that conducting research made them nervous, anxious and scared (Amoo & Gbadamosi, 2021;Muzzmal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%